ENTERPRISE THEORY AND CORPORATE BALANCE SHEETS. - Suojanen, Waino W. (The Accounting Review, 1958)
The article presents a study that highlights the separation within the group of functions of management from those of ownership and the concentration of the former in a few hands. It has resulted in fact in a large share of profits being retained in the business. The owners have little opportunity to dispose these profits as they would if the profit were all distributed in dividends. 29.4 per cent of their net income is retained within the larger corporation during the period 1922 to 1927. This retention may be intended to avoid shortages of liquid resources in periods of restricted business or to permit the continued payment of dividends in the absence of adequate current profits. But it also facilitates expansion without the necessity of issuing new securities. Those managers who find size attractive can satisfy their desire without having to submit their plans to the test of the capital market. The study asserts that if the corporation is to grow, investment opportunities must be deliberately created and continuously available.